Patient Perceptions of Text Messaging to Improve Antiretroviral Therapy Adherence: A Qualitative Study of Patients in a Ryan White Clinic. (22nd February 2018) - Sherman, Elizabeth; Clauson, Kevin Alan; Elrod, Shara; Eckardt, Paula; Alkhateeb, Fadi; Jacobs, Robin
Evidence on the use of short message service (SMS) to improve medication adherence in people living with HIV (PLHIV) is mounting, yet qualitative research on patient perceptions regarding SMS content and utility for HIV/AIDS remains nascent. To explore the experience of receiving medication reminders via SMS among PLHIV, 45 uninsured and underinsured PLHIV nested within the intervention arm of a larger study received daily, 1-way SMS adherence reminders. Qualitative data were collected by face-to-face, structured interview and were analyzed using conventional content analysis methods. Three main themes emerged from the data: (1) reminders helping with adherence, (2) concerns about delivery modes, and (3) the need for confidentiality. Study findings offer enhanced focus on an emerging strategy in patient-centered HIV care: Equipped with greater context on the experiences of PLHIV using SMS adherence reminders, health-care providers can offer more targeted support and thereby maximize the benefits of this popular and powerful technology.